Synthesis of a Series of Novel 2-Amino-5-substituted 1,3,4-oxadiazole and 1,3,4-thiadiazole Derivatives as Potential Anticancer, Antifungal and Antibacterial Agents - Pham, Em C.; Truong, Tuyen Ngoc; Dong, Nguyen Hanh; Vo, Duy Duc; Hong Do, Tuoi Thi (Medicinal Chemistry, 2022)
Background: Many compounds containing a five-membered heterocyclic ring display exceptional chemical properties and versatile biological activities. Objective: The objective of the present study was to prepare the 5-substituted 2-amino-1,3,4- oxadiazole and 2-amino-1,3,4-thiadiazole derivatives and evaluate their potential anticancer, antibacterial and antifungal activities. Methods: Twenty-seven derivatives were synthesized by iodine-mediated cyclization of semicarbazones or thiosemicarbazones obtained from condensation of semicarbazide or thiosemicarbazide and aldehydes. The structures were confirmed by 1H-NMR, 13C-NMR and MS spectra. The antibacterial and antifungal activities were evaluated by diffusion method and the anticancer activities were evaluated by MTT assay. Results: Twenty-seven derivatives have been synthesized in moderate to good yields. A number of derivatives exhibited potential antibacterial, antifungal and anticancer activities. Conclusion: Compounds (1b, 1e and 1g) showed antibacterial activity against Streptococcus faecalis, MSSA and MRSA with MIC value ranging between 4 to 64 μg/mL. Compound (2g) showed antifungal activity against Candida albicans (8 μg/mL) and Aspergillus niger (64 μg/mL). Compound (1o) exhibited high cytotoxic activity against HepG2 cell line (IC50 value 8.6 μM) which is comparable to the activity of paclitaxel, and is non-toxic on LLC-PK1 normal cell line. The structure activity relationship and molecular docking study of the synthesized compounds have also been reported.
Keywords: 1